PENGARUH PENAMBAHAN TEPUNG REBUNG (Gigantochloa apus) TERHADAP MUTU MIE BASAH - Eka Andrasari; Lahming Lahming; Ratnawaty Fadilah (Universitas Negeri Makassar, 2019)
This study aims to determine the effect of adding bamboo shoot flour to moisture content, ash content, protein, fiber, potassium and hedonic quality. The sample used that is noodles with a variation of the concentration of bamboo shoot flour 10%, 15% and 20%. This research is a quantitative research (experiment) with Completely Randomized Design (RAL) one factor with 3 treatments conducted as many as 3 times replications. The analytical technique used in this study was the analysis of variance which analyzed using SPSS version 22. The results showed that for water content, ash content, protein, fiber, potassium and hedonic quality were most preferred by panelists namely in treatment C with the addition of bamboo shoot flour 30g